Charge-carrier mobilities in metal halide perovskites: Fundamental mechanisms and limits - Herz, L (American Chemical Society, 2017)
Perovskite photovoltaic cells have seen a remarkable rise in power conversion efficiencies over a period of only a few years. Much of this performance is underpinned by the favorable chargecarrier mobilities in metal halide perovskites (MHPs), which are remarkably high for materials with such facile and versatile processing routes. This Perspective outlines the mechanisms that set a fundamental upper limit to charge-carrier mobility values in MHPs and reveals how they may be tuned through changes in stoichiometry. In addition, extrinsic effects such as grain size, energetic disorder, and self-doping are discussed for specific MHPs in the context of remedies designed to avoid them.